FEATURES OF PSYCHIC DEVELOPMENT IN PRESCHOOL AGE (Universal International Scientific Journal, 2026)
This article scientifically and theoretically analyzes the laws of mental development of preschool children, the role of play, which is a leading type of activity, in the formation of personality, and the specificity of cognitive processes, and provides practical recommendations.
Keywords: Preschool age; mental development; play activities